Quadriceps muscle atrophy after non-invasive anterior cruciate ligament injury: evidence linking to autophagy and mitophagy - Noh, Sung Gi; Ahn, Ahram; Davi, Steven M.; Lepley, Lindsey K.; Kwon, Oh Sung (Frontiers in Physiology, 2024)
Introduction: Anterior cruciate ligament (ACL) injury is frequently accompanied by quadriceps muscle atrophy, a process closely linked to mitochondrial health and mitochondria-specific autophagy. However, the temporal progression of key quadricep atrophy-mediating events following ACL injury remains poorly understood. To advance our understanding, we conducted a longitudinal study to elucidate key parameters in quadriceps autophagy and mitophagy. Methods: Long-Evans rats were euthanized at 7, 14, 28, and 56 days after non-invasive ACL injury that was induced via tibial compression overload; controls were not injured. Vastus lateralis muscle was extracted, and subsequent immunoblotting analysis was conducted using primary antibodies targeting key proteins involved in autophagy and mitophagy cellular processes. Results: Our findings demonstrated dynamic changes in autophagy and mitophagy markers in the quadriceps muscle during the recovery period after ACL injury. The early response to the injury was characterized by the induction of autophagy at 14 days (Beclin1), indicating an initial cellular response to the injury. Subsequently, at 14 days we observed increase in the elongation of autophagosomes (Atg4B), suggesting a potential remodeling process. The autophagosome flux was also augmented between 14- and 28 days (LC3-II/LC3-I ratio and p62). Notably, at 56 days, markers associated with the elimination of damaged mitochondria were elevated (PINK1, Parkin, and VDAC1), indicating a possible ongoing cellular repair and restoration process. Conclusion: These data highlight the complexity of muscle recovery after ACL injury and underscore the overlooked but crucial role of autophagy and mitophagy in promoting the recovery process.